Pedagogical Considerations for a Critical Understanding of School Learning: A Perspective from the Context of the School itself - Rubio, Carlos Eliecer Vocar (Journal of Posthumanism, 2025)
The present research aims at developing a critical and authentic pedagogical understanding of school learning. It stems from the understanding that the nature of learning and how it occurs in the school context has direct implications on the design, organization and implementation of teaching. Learning is conceived not as a product, an activity or a specific content, but as a process consciously directed to the selection/appropriation of social culture. In the same way, it defines the transforming potential of learning, both of the subject who learns and of the reality in which he/she acts. Methodologically, it is based on the qualitative epistemology of Fernando González Rey, defining knowledge as a constructive-interpretative production that occurs in the relationship between the researcher, the protagonists and the practice itself, highlighting the meaning of singularity as a legitimate level of production of pedagogical scientific knowledge. The study considered three complementary lines of work: critical analysis of more than a hundred published works on learning; exhaustive analysis of all the official documents that define the Chilean normative framework; and implementation of a co-constructive process, which summoned more than a hundred teachers, managers and assisting professionals from different regions of the country. This research seeks to contribute to the design of a theoretical model of school learning, which allows correcting conceptual errors, as well as the biased orientations that emanate from the central level regarding school learning.